D/H in beetle chitin from the late-glacial Lismore site in eastern Canada: supplementary note - Miller, Randall (Atlantic Geology, 1994)
D/H (Deuterium-Hydrogen) analysis of chitin from a late-glacial site in eastern Canada demonstrates promising results and lends support to other evidence for the Killarney Oscillation.